2005
DOI: 10.1074/jbc.m502849200
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of an Anti-cancer Lysophospholipid through Selective Modification of Lipid Raft Composition

Abstract: Edelfosine is a prototypical member of the alkylphosphocholine class of antitumor drugs. Saccharomyces cerevisiae was used to screen for genes that modulate edelfosine cytotoxicity and identified sterol and sphingolipid pathways as relevant regulators. Edelfosine addition to yeast resulted in the selective partitioning of the essential plasma membrane protein Pma1p out of lipid rafts. Microscopic analysis revealed that Pma1p moved from the plasma membrane to intracellular punctate regions and finally localized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
115
0
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(123 citation statements)
references
References 50 publications
2
115
0
4
Order By: Relevance
“…Indicating that phosphorylation and lipid raft association may play important roles in maintaining protein stability at the plasma membrane [19,20]. This view is consistent with the fact that disruption of membrane microdomains at the plasma membrane by incubation with the anti-cancer drug edelfosine, an alkylglycerophosphocholine, disrupts raft association of plasma membrane localized Pma1 and induces its vacuolar turnover [21].…”
Section: Biogenesis and Transport Of The Proton Pumping H D -Atpasesupporting
confidence: 71%
“…Indicating that phosphorylation and lipid raft association may play important roles in maintaining protein stability at the plasma membrane [19,20]. This view is consistent with the fact that disruption of membrane microdomains at the plasma membrane by incubation with the anti-cancer drug edelfosine, an alkylglycerophosphocholine, disrupts raft association of plasma membrane localized Pma1 and induces its vacuolar turnover [21].…”
Section: Biogenesis and Transport Of The Proton Pumping H D -Atpasesupporting
confidence: 71%
“…We have previously shown that edelfosine increases cytosolic [Ca 2 þ ] in HeLa cells (Nieto-Miguel et al, 2007). On these grounds, and taking into account the interaction of edelfosine with cell membranes and lipids (Gajate et al, , 2009a(Gajate et al, , 2009bZaremberg et al, 2005;Mollinedo and Gajate, 2006;Torrecillas et al, 2006;Busto et al, 2007Busto et al, , 2008Ausili et al, 2008;, it might be envisaged that the increase in cytosolic [Ca 2 þ ] could be due to an increased permeability of the plasma membrane, resulting in Ca 2 þ entry from the extracellular medium, which it then leads to the herein reported increase in [Ca 2 þ ] ER , well above the steady state levels in control cells. The effect on [Ca 2 þ ] ER may seem puzzling, because ER stress has been rather associated with ER-stored Ca 2 þ release.…”
Section: Discussionmentioning
confidence: 98%
“…Such modifications can be used for therapeutic purposes, an approach termed ''membrane-lipid therapy'' (7,24). Indeed, lipid molecules such as edelfosine and mitelfosine are potent antineoplastic drugs that target the membrane (25,26), and they induce apoptosis in cancer cells through mechanisms that alter membrane lipid raft organization (26). By contrast with oleic acid, ␣-hydroxy derivatives of fatty acids (e.g., HOA) are less prone to be used by cells, and they are therefore likely to display better pharmacological properties (27).…”
Section: Discussionmentioning
confidence: 99%